Rights and realities. - Ain o Salish Kendra(Dhaka, Bangladesh) (Dhaka : Ain o Salish Kendra, 1997)
Contributed articles on legal, social and political issues raised in national and international debates; with special reference to Bangladesh.
Includes bibliographical references.
Keywords: Civil rights -- Bangladesh; Human rights; Human rights -- Bangladesh